Patient, family and provider views of measurement-based care in an early-psychosis intervention programme. Issue 5 (17th September 2021) - Cuperfain, Ari B.; Hui, Katrina; Berkhout, Suze G.; Foussias, George; Gratzer, David; Kidd, Sean A.; Kozloff, Nicole; Kurdyak, Paul; Linaksita, Brandon; Miranda, Dielle; Soklaridis, Sophie; Voineskos, Aristotle N.; et al.
Abstract : Background: Measurement-based care (MBC) in mental health improves patient outcomes and is a component of many national guidelines for mental healthcare delivery. Nevertheless, MBC is not routinely integrated into clinical practice. Several known reasons for the lack of integration exist but one lesser explored variable is the subjective perspectives of providers and patients about MBC. Such perspectives are critical to understand facilitators and barriers to improve the integration of MBC into routine clinical practice. Aims: This study aimed to uncover the perspectives of various stakeholders towards MBC within a single treatment centre. Method: Researchers conducted qualitative semi-structured interviews with patients ( n = 15), family members ( n = 7), case managers ( n = 8) and psychiatrists ( n = 6) engaged in an early-psychosis intervention programme. Data were analysed using thematic analysis, informed by critical realist theory. Results: Analysis converged on several themes. These include (a) implicit negative assumptions; (b) relevance and utility to practice; (c) equity versus flexibility; and (d) shared decision-making. Providers assumed patients' perspectives of MBC were negative. Patients' perspectives of MBC were actually favourable, particularly if MBC was used as an instrument to engage patients in shared decision-making and communication rather than as a dogmatic and rigid clinical decision tool. Conclusions: This qualitative study presents the views of various stakeholders towards MBC, providing an in-depth examination of the barriers and facilitators to MBC through qualitative investigation. The findings from this study should be used to address the challenges organisations have experienced in implementing MBC.